Chronic suppurative otitis media: disrupted host-microbial interactions and immune dysregulation - Yuan, Vincent G.; Xia, Anping; Santa Maria, Peter L. (Frontiers in Immunology, 2025)
Recent research has uncovered new mechanisms that disrupt the balance between the host and microbes in the middle ear, potentially leading to dysbiosis and chronic suppurative otitis media (CSOM). Dysbiotic microbial communities, including core pathogens such as persister cells, are recognized for displaying cooperative virulence. These microbial communities not only evade the host’s immune defenses but also promote inflammation that leads to tissue damage. This leads to uncontrolled disorder and pathogen proliferation, potentially causing hearing loss and systemic complications. In this discussion, we examine emerging paradigms in the study of CSOM that could provide insights into other polymicrobial inflammatory diseases. Additionally, we underscore critical knowledge gaps essential for developing a comprehensive understanding of how microbes interact with both the innate and adaptive immune systems to trigger and maintain CSOM.